The influence of green shared vision, education and training, and green recruitment, on organizational citizenship behavior for environment in elementary schools in Indonesia. - Nur Rahman, Reny; Permana, Asep Rokhyadi (Journal of Management and Business Education, 2023)
Managing human resources in schools as a basis for instilling knowledge becomes a strategic phenomenon. The importance of these human resources needs to start with a sustainable development plan, with green regulations and a green environment. Analysis of the influence of Green Shared Vision, Education and Training and Green Recruitment on Organizational Citizenship Behavior for the Environment is the main objective of this research. To achieve the research objectives, the object of this study were all elementary school employees, Yogyakarta Province - Indonesia, with a sample calculation using the slovin method of 163 workers in the school. Retrieval of data using purposive random sampling method and cluster sampling technique. With 23 indicators of 4 variables measured by simantec scale. The analysis tools used are validity and reliability, using Variance Based Structural Equation Modeling (SEM) analysis, with the SmartPLS version 4 software tool. The research results show that Green Shared Vision has no effect on Organizational Citizenship Behavior for Environment, Education and Training, Green Recruitment has a positive and significant effect on Organizational Citizenship Behavior for Environment.